Stenotrophomonas maltophilia infections in intensive care units: a prospective and international ID-IRI study - Çaşkurlu, Hülya; Çağ, Yasemin; Ankaralı, Handan; Tahmaz, Alper; Vatansever, Gökhan; Bilir, Yeşim Aybar; Erdem, Hakan (Journal of Infection in Developing Countries, 2026)
Introduction: Stenotrophomonas maltophilia (S. Maltophilia) is a multidrug-resistant pathogen causing severe infections in intensive care units (ICUs). This study aimed to identify the risk factors influencing 30-day mortality and evaluate antimicrobial susceptibility patterns in ICU patients with S. maltophilia infections. Methodology: A prospective, multicenter, international observational study was conducted between 15 October 2023 and 15 April 2024, in 36 ICUs across 12 countries. Adult patients (? 18 years) with S. maltophilia isolated from blood, urine, or respiratory cultures were included if isolates were considered clinically consistent with infection. Colonized or coinfected patients were excluded. Clinical, laboratory data were collected prospectively. Thirty-day outcome was defined as survival or death after the first positive culture. Results: A total of 207 patients were included; 109 (52.7%) died within 30 days. The primary infection sites were pneumonia (28.5%) and bloodstream infections (38.0%). Resistance rates were 7.2% for trimethoprim-sulfamethoxazole (TMP-SMX), 10.4% for levofloxacin, and 27% for ceftazidime. None of the patients received effective empiric therapy. Older age (p = 0.030), acute renal failure (p = 0.016), chronic obstructive pulmonary disease (COPD; p = 0.008), malignancy (p = 0.001), and sequential organ failure assessment (qSOFA) ? 2 (p = 0.001) were independently associated with higher mortality. Repeat culturing and antimicrobial modification according to susceptibility testing reduced mortality (p = 0.017). Conclusions: S. maltophilia remains a lethal ICU pathogen. Early risk assessment, cultures, susceptibility testing, and therapy changes are vital. TMP-SMX and levofloxacin stay effective; but surveillance, infection control, and prudent antibiotic use remain essential. © 2026 Çaşkurlu et al.
Keywords: intensive care unit (ICU); maltophilia; mortality; risks